Oxygen exposure effects on the dechlorinating activities of a trichloroethene-dechlorination microbial consortium. (September 2017) - Liu, Na; Li, Haijun; Li, Mengyan; Ding, Longzhen; Weng, Chih-Huang; Dong, Cheng-Di
Graphical abstract: Highlights: Dehalococcoides mccartyi (Dhc) exposed to O2 could degrade TCE to ETH. tceA gene-Dhc was less sensitive to O2 exposure than vcrA gene-Dhc. Non-dechlorinators were crucial to scavenge O2 to protect Dhc from being damaged. Abstract: The aim of this work was to study the effects of the presence of oxygen on the dechlorination of trichloroethene by a microbial consortium containing D. mccartyi . The 16S rRNA and reductive dechlorination genes of the functional bacteria and the non-dechlorinators were monitored. Exposing the consortium to oxygen altered the overall biotransformation rate of the dechlorination process, biotransformation processes prolonged with oxygen concentrations changing from 0 to 7.2 mg/L, however, trichloroethylene was eventually dechlorinated to ethene. The qPCR analyses revealed that the D. mccartyi strains containing the tceA gene were less sensitive to exposure to oxygen than were the D. mccartyi strains containing the vcrA gene. High-throughput sequencing by Illumina MiSeq indicated that the non-dechlorinating organisms were probably crucial to scavenge the oxygen to protect D. mccartyi from being damaged.